Recurrent CNTN1 antibody-positive nodopathy: a case report and literature review - Zhao, Min; Chen, Guixian; Li, Shuguang; Li, Xiaojun; Chen, Haoxuan; Lou, Zhenzhen; Ouyang, Huiying; Zhan, Yibo; Du, Chenghao; Zhao, Yuanqi (Frontiers in Immunology, 2024)
Background: Contactin-1 (CNTN1) antibody-positive nodopathy is rare and exhibits distinct clinical symptoms such as tremors and ataxia. However, the mechanisms of these symptoms and the characteristics of the cerebral spinal fluid (CSF) remain unknown.Case Presentation: Here, we report a case of recurrent CNTN1 antibody-positive nodopathy. Initially, a 45-year-old woman experiencing numbness in the upper limbs and weakness in the lower limbs was diagnosed with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Eleven years later, her symptoms worsened, and she began to experience tremors and ataxia. Tests for serum CNTN1, GT1a, and GQ1b antibodies returned positive. Subsequently, she was diagnosed with CNTN1 antibody-positive nodopathy and underwent plasmapheresis therapy, though the treatment's efficacy was limited. To gain a deeper understanding of the disease, we conducted a comprehensive literature review, identifying 52 cases of CNTN1 antibody-positive nodopathy to date, with a tremor prevalence of 26.9%. Additionally, we found that the average CSF protein level in CNTN1 antibody-positive nodopathy was 2.57 g/L, with 87% of patients exhibiting a CSF protein level above 1.5 g/L.Conclusion: We present a rare case of recurrent CNTN1 antibody-positive nodopathy. Our findings indicate a high prevalence of tremor (26.9%) and elevated CSF protein levels among patients with CNTN1 antibody-positive nodopathy.